2013
DOI: 10.1142/s0218271813500399
|View full text |Cite
|
Sign up to set email alerts
|

On the Triple Interacting Dark Energy Model

Abstract: Three aspects of the triple interacting dark energy model are studied. The relation between two types of the triple interacting dark energy models is investigated first. Then, the concrete forms of the interacting terms are given by supposing ratios between different energy components is stationary. Furthermore, the stability of the triple interacting dark energy model with different transfer terms is studied in detail, and the complete table of relations between the stability and the transfer terms is given, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Similar attempts in f (G) and f (T ) gravities can be found in [41,42] respectively. A study of triple interacting DE model can be found in [43].…”
Section: Basic Equations Of F(rt) Gravitymentioning
confidence: 99%
“…Similar attempts in f (G) and f (T ) gravities can be found in [41,42] respectively. A study of triple interacting DE model can be found in [43].…”
Section: Basic Equations Of F(rt) Gravitymentioning
confidence: 99%
“…al attempted to saponify the distillation residue [5] so as to recover isooctanol, but a large amount of organic wastewater is inevitably generated. Huang et al employed Zn powder to reduce dithiodiacetic acid that was formed during the synthesis of thioglycolic acid from sodium chloroacetate and sodium thiosulfate, founding that the Zn reduction could significantly enahnce the yield of thioglycolic acid [6] . These results reveal that breaking disulfide bond is feasible.…”
Section: Introductionmentioning
confidence: 99%